Rate of Changes in CMT Neuropathy and Examination Scores in Japanese Adult CMT1A Patients - Kitani-Morii, Fukiko; Noto, Yu-ichi; Tsuji, Yukiko; Shiga, Kensuke; Mizuta, Ikuko; Nakagawa, Masanori; Mizuno, Toshiki (Frontiers in Neurology, 2020)
Introduction: We aimed to clarify the clinical characteristics of adult patients with Charcot-Marie-Tooth disease type 1A (CMT1A), especially those diagnosed at middle or advanced ages. Methods: Medical records of CMT1A outpatients between 2012 and 2019 were reviewed. The age at onset, age at the initial hospital visit, and rate of disease progression assessed based on the CMT neuropathy score (CMTNS) were analyzed. Results: Among 45 adult CMT1A patients, 45% had been diagnosed after 50 years of age, whereas 95% of all patients had exhibited some CMT-related symptoms before 20 years of age. The annual increase of CMTNS did not differ between patients under and over 50 years (0.54±0.21 vs. 0.82±0.23, respectively, p = 0.24). To determine whether patients diagnosed at a young age have a higher deterioration rate, patients were classified into three groups according to their current age and age at diagnosis: patients under 50 years of age, patients aged over 50 years of age but diagnosed before 50, and patients diagnosed after 50 years of age. The mean annual increase of CMTNS, however, did not differ among these groups (0.54±0.21 vs. 0.60±0.52 vs. 0.93±0.24, respectively, p = 0.27). Discussion: Despite having symptoms in childhood, a certain number of CMT1A patients were diagnosed at an advanced age. Understanding the existence of undiagnosed patients at all ages is important for early intervention of physical therapy and avoiding neurotoxic medication for CMT1A.